2015
DOI: 10.1620/tjem.236.289
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of TAFRO Syndrome, a Variant of Multicentric Castleman’s Disease, with Cyclosporine A: Possible Pathogenetic Contribution of Interleukin-2

Abstract: Multicentric Castleman's disease is a systemic inflammatory disorder characterized by lymphadenopathy and excessive interleukin-6 production. A unique clinicopathologic variant of multicentric Castleman's disease, TAFRO (i.e., thrombocytopenia, anasarca, fever, renal failure or reticulin fibrosis, and organomegaly) syndrome, was recently proposed in Japan. Despite the successful use of anti-interleukin-6 therapy in some patients with TAFRO syndrome, not all patients achieve remission. The pathophysiological et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…In the 2015 treatment strategy for TAFRO syndrome (26), treatments with high-dose glucocorticoids, cyclosporin A, tocilizumab, and rituximab are recommended, based on the clinical experiences of Japanese research teams. In previous reports describing the clinical courses of six TAFRO syndrome cases (7,11,15-17,19), treatment with rituximab was effective, except in one case (15). To our knowledge, our Case 2 is the second case of tocilizumab-resistant TAFRO syndrome successfully treated with rituximab (19).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In the 2015 treatment strategy for TAFRO syndrome (26), treatments with high-dose glucocorticoids, cyclosporin A, tocilizumab, and rituximab are recommended, based on the clinical experiences of Japanese research teams. In previous reports describing the clinical courses of six TAFRO syndrome cases (7,11,15-17,19), treatment with rituximab was effective, except in one case (15). To our knowledge, our Case 2 is the second case of tocilizumab-resistant TAFRO syndrome successfully treated with rituximab (19).…”
Section: Discussionmentioning
confidence: 81%
“…These findings suggested that IL-6 may not be the primary pathological cytokine (20). Konishi et al (15) also suggested the involvement of an IL-2-dependent pathway in addition to IL-6-related pathways in the etiology of TAFRO syndrome, based on their clinical experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our case thus represented a very rare case of successful treatment for grade 5 TAFRO syndrome. Some patients with TAFRO syndrome have been successfully treated with steroid, immunosuppressants, including cyclosporine A (CyA), TCZ and rituximab, and/or immunomodulatory drugs like thalidomide [2][3][4][5][6]. According to the 2015 treatment strategy for TAFRO syndrome, steroid is the first-line treatment, with CyA as the second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Konishi et al suggested that IL-2-related immunological abnormality plays a role in the pathogenesis of TAFRO syndrome, in addition to IL-6 [4]. Their case achieved remission with CyA and CyA interferes in T cell activity via inhibition of calcineurin which is responsible for activating IL-2 encoding gene transcription [10].…”
Section: Discussionmentioning
confidence: 99%